Anatomically Contoured Anterior Plating for Isolated Tibiotalar Arthrodesis: A Systematic Review. Issue 4 (August 2017) - Kusnezov, Nicholas; Dunn, John C.; Koehler, Logan R.; Orr, Justin D.
Introduction. We performed a systematic review of the published literature to characterize patient demographic, surgical techniques, and functional outcomes to elucidate the complication and revision rates following isolated tibiotalar arthrodesis with anatomically contoured anterior plating. Methods. A comprehensive literature search was performed. Inclusion criteria were peer-reviewed studies in English, after 1990, at least 10 patients, and reporting clinical outcomes following contoured anterior plating and with follow-up of at least 80% and 1 year. Primary outcomes were fusion rate, time to fusion, return to activities, satisfaction, and functional outcome scores. Complication rates, reoperation, and revision were also extracted. Results. Eight primary studies with 164 patients met the inclusion criteria. The average sample size was 21 ± 10.0 patients and average age was 49.2 years with 61.6% male. Posttraumatic arthritis (49.4%) was the most common operative indication, followed by primary osteoarthrosis (18.9%). The average follow-up was 21.1 months. At this time, 97.6% of patients went on to uneventful union at a weighted average time of 18.7 weeks postoperatively. AOFAS scores improved significantly ( P < .05). 25% complication rate was reported with wound complication (7.9%) and hardware irritation (6.7%) most common. Overall, 21.3% of patients underwent reoperation; 4 for revision arthrodesis following nonunion. Conclusion. Isolated tibiotalar arthrodesis utilizing anatomically contoured anterior plating demonstrates excellent clinical and functional outcomes at short-term follow-up. Overall, 97.6% of patients went on to fusion and functional outcomes consistently improved following surgery. Furthermore, while one-quarter of patients experienced complications, wound complications were relatively uncommon and less than one-quarter of these required surgical intervention. Levels of Evidence: Level IV: Systematic Review